Flourishing Pasien Hipertensi: Adakah Peranan Relasi Sosial di Dalamnya? - Pratama, Okik Yoga; Rina, Amherstia Pasca; Noviekayati, IGAA; Syaharani, SRK (Buletin Riset Psikologi dan Kesehatan Mental, 2025)
Hypertension recorded as the fifth non-communicable disease (NCD) that became a major health problem in Indonesia. This study investigated the association between social relationships and flourishing among individual with hypertension. This study used a cross-sectional method involving 109 participants with hypertension at the Pasuruan City Police Pratama Clinic. The flourishing level was measured with the Flourishing Index scale and social relation is measured with the NIH Toolbox Adult Social Relationship. The results showed that there was a positive relationship between social relations and flourishing among individuals with hypertension (r = 0.437, p < 0.01), which indicates that the better the individual's social relations, the better the individual's flourishing.